2022
DOI: 10.15604/ejss.2022.10.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media Marketing on Purchase Intention of Skincare Products Among Indonesian Young Adults

Abstract: This study aims to investigate the impact of social media marketing activities (SMMAs) on purchase intention of skincare products among Indonesian young adults. The secondary objective of this study is to investigate the mediating effect of subjective norms, perceived behavioral control, brand awareness, and social brand engagement on the relationship between social media marketing activities on purchase intention of skincare products. Despite its popularity in the Indonesian market, the study on the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This is an example: "The products and services of restaurant x represent excellent value for money." Regarding the measurements of followers' purchase intention, an adapted three-item scale developed by Emini and Zeqiri [84] and adopted by Chrisniyanti and Fah [4] was utilized. A sample of this scale is: "I plan to purchase restaurant products that I have seen on social media."…”
Section: Measures and Instrument Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an example: "The products and services of restaurant x represent excellent value for money." Regarding the measurements of followers' purchase intention, an adapted three-item scale developed by Emini and Zeqiri [84] and adopted by Chrisniyanti and Fah [4] was utilized. A sample of this scale is: "I plan to purchase restaurant products that I have seen on social media."…”
Section: Measures and Instrument Developmentmentioning
confidence: 99%
“…Through these platforms, businesses can create content that is tailored to their target audience and share it with their followers [2]. Additionally, businesses can use social media to run targeted ads that are tailored to specific audiences and assess their campaign's success [3,4]. Businesses can also use social media to gain valuable insights into customer behavior and preferences for future marketing campaigns [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sample of these items is "Overall, I am satisfied with this restaurant". To measure followers' purchase intentions, a three-item scale based on Chrisniyanti and Fah [78] was utilized. An example of one of these items might be "I plan to purchase products that I have seen advertised through social media".…”
Section: Measures and Instrument Developmentmentioning
confidence: 99%
“…Research by Dove in Indonesian Beauty Confidence Report 2017 found that 84% of Indonesian women do not feel beautiful (Herawati & Dara, 2022). This desire to be physically attractive and beautiful influences many young Indonesian adults to be more concerned about their appearance and makes them consume skincare products daily, which aims to boost their confidence levels (Chrisniyanti & Fah, 2022).…”
Section: A Introductionmentioning
confidence: 99%